Closing the gap in family leisure provision: giving leisure facility managers the opportunity to reflect on what they provide for families. Issue 1 (2nd January 2016) - Lamb, David
Abstract : The research literature on family leisure has been dominated by the views of participants in family leisure activities, so the purpose of this study was to give leisure facility managers an opportunity to reflect on the issue of family leisure from a provider perspective to address the imbalance. Leisure facility managers operating in different areas of leisure provision play a pivotal role in enacting leisure policy into a range of leisure programmes and activities for families. Their opinions and knowledge concerning family leisure needs are significant, as they help shape and determine the nature of family leisure provision in the facilities they manage. The literature review on which this study is based identified five key areas of research in family leisure (concept of leisure, constraints, parenting, work–life balance and dualities of family leisure). As a result of the interviews with leisure facility managers, six key themes emerged (concept, constraints, empathy, customers/community, family friendly and design). In concluding, suggestions are made based on the feedback given by leisure facility managers to effect change and enhance leisure provision for families and recommendations for new avenues of research in family leisure are given.